Anthocyanins From Clitoria ternatea Flower: Biosynthesis, Extraction, Stability, Antioxidant Activity, and Applications - Vidana Gamage, Gayan Chandrajith; Lim, Yau Yan; Choo, Wee Sim (Frontiers in Plant Science, 2021)
Clitoria ternatea plant is commonly grown as an ornamental plant and possesses great medicinal value. Its flower is an edible flower and also known as blue pea or butterfly pea flower. The unique feature of anthocyanins present in blue pea flower is the high abundance of polyacylated anthocyanins known as ternatins. Ternatins are polyacylated derivatives of delphinidin 3,3',5'-triglucoside. This review covers the biosynthesis, extraction, stability, antioxidant activity and applications of anthocyanins from Clitoria ternatea flower. Hot water extraction of dried or fresh petals of blue pea flower could be employed successfully to extract anthocyanins from blue pea flower for food application. Blue pea flower anthocyanins showed good thermal and storage stability, but less photo stability. Blue pea flower anthocyanins also showed an intense blue colour in acidic pH between pH 3.2 to pH 5.2. Blue pea flower anthocyanin extracts demonstrate significant in vitro and cellular antioxidant activities. Blue pea flower anthocyanins could be used as a blue food colourant in acidic and neutral foods. Incorporation of blue pea flower anthocyanins in food increased the functional properties of food such as antioxidant and antimicrobial properties. Blue pea flower anthocyanins have also been used in intelligent packaging. A comparison of blue pea flower anthocyanins with two other natural blue colouring agents used in the food industry, spirulina or phycocianin and genipin-derived pigments is also covered. Anthocyanins from blue pea flower are promising natural blue food colouring agent.